Theoretical Model to Evaluate the Impact of Consumer Behaviour on Business Performance - Ramos, Pedro Costa; Lopes, Paula (International Review of Management and Marketing, 2025)
This paper focuses on the problematic of how the different factors that tend to influence consumer behaviour: sociocultural; economic; personal; psychological, can positively affect the innovation cycle and, consequently, the business performance, in both quantitative and qualitative terms. Based on the existing literature, a theoretical model was conceptualized. This model, supported by nine operational propositions, was called “Model for the Evaluation of the Impact of Consumer Behaviour on Business Performance,” because of the role that the factors system assumes on its execution and its consequent relation with the innovation cycle and business performance dimension. Following an empirical-formal methodology, the investigation process involved the collection of data through a questionnaire, applied to a representative set of SME’s from the Portuguese economic fabric - resorting to a sampling universe associated companies of the Portuguese Entrepreneurial Association (AEP). It ́s our objective and conviction, after the estimation process, through the application of a modelling process based on structural equations, to confirm the existence of positive and statistically relevant effects among the three dimensions that make up the developed model.